Saposins modulate human invariant Natural Killer T cells self-reactivity and facilitate lipid exchange with CD1d molecules during antigen presentation. - Salio, M; Ghadbane, H; Dushek, O; Shepherd, D; Cypen, J; Gileadi, U; Aichinger, M; Napolitani, G; Qi, X; Van Der Merwe, P; Wojno, J; Veerapen, N; et al. (2013)
Lipid transfer proteins, such as molecules of the saposin family, facilitate extraction of lipids from biological membranes for their loading onto CD1d molecules. Although it has been shown that prosaposin-deficient mice fail to positively select invariant natural killer T (iNKT) cells, it remains unclear whether saposins can facilitate loading of endogenous iNKT cell agonists in the periphery during inflammatory responses. In addition, it is unclear whether saposins, in addition to loading, also promote dissociation of lipids bound to CD1d molecules. To address these questions, we used a combination of cellular assays and demonstrated that saposins influence CD1d-restricted presentation to human iNKT cells not only of exogenous lipids but also of endogenous ligands, such as the self-glycosphingolipid β-glucopyranosylceramide, up-regulated by antigen-presenting cells following bacterial infection. Furthermore, we demonstrated that in human myeloid cells CD1d-loading of endogenous lipids after bacterial infection, but not at steady state, requires trafficking of CD1d molecules through an endo-lysosomal compartment. Finally, using BIAcore assays we demonstrated that lipid-loaded saposin B increases the off-rate of lipids bound to CD1d molecules, providing important insights into the mechanisms by which it acts as a "lipid editor," capable of fine-tuning loading and unloading of CD1d molecules. These results have important implications in understanding how to optimize lipid-loading onto antigen-presenting cells, to better harness iNKT cells central role at the interface between innate and adaptive immunity.